‘Learning journeys’ for adaptive management – Where does it take us? - Ørnemark, Charlotte (Global Partnership for Social Accountability, 2016)
Keywords: IMPORTANT

What about the results? Lessons from long-term process support to strengthen results-based management (RBM) for Swedish framework NGOs operating in Western Balkans - Ørnemark, Charlotte (NCG, 2012)
The observations and lessons outlined in this report should be seen as a contribution to the on-going learning and reflections in a wider debate on how to assess and monitor results from support to CSOs involved in complex social change processes (as opposed to those involved in more ‘classical’ service delivery and more linear development assistance). These lessons, though directly emerging from the consultancy to provide long-term RBM support to the FOs and their local CSO partners in Western Balkans, also draws on previous experiences and similar lessons from on-going initiatives. In brief, these lessons call for a certain ‘paradigm shift’ in the way we (as development professionals) regard and support RBM for actors involved in less tangible social change processes in highly contested political spaces. Some of these shifts, outlined in more detail in different sections of this report, are summarised below:  From a linear, aggregated cause-and-effect thinking around RBM to one that is linked to human factors and is embedded in systems,  From pushing the burden of reporting down in the system to a clearer division of labour between donors, recipient governments, intermediary agents like framework NGOs (FOs) and implementing CSOs with each actor using its comparative advantage and appropriate role in the RBM process and for its own learning,  From operating in programming and results frameworks where outcomes and impact are largely assumed to be predictable to setting up systems that deal with uncertainty and that capture emerging result patterns through tracking of gradual changes,  From a project/programme perspective to a focus on institutions and systems as actors and arenas for change, where organisations are enabled to act as change agents towards clearly identified processes of social transformation,  From SMART to REAL results frameworks – although SMART (specific, measurable, achievable, realistic and time-bound) principles are always good to keep in mind for the formulation of goals and indicators, the danger of coming up with fictive measuring frameworks calls for a more systematic incorporation of ‘real’ concerns, including making RBM processes rights-based, embedded in local realities (and empowering for those involved), aligned to national reform efforts and national and international human rights commitments, and learning-oriented for all different levels of operations.